Differential gene expression in dentate granule cells in mesial temporal lobe epilepsy with and without hippocampal sclerosis. (22nd January 2016) - Griffin, Nicole G.; Wang, Yu; Hulette, Christine M.; Halvorsen, Matt; Cronin, Kenneth D.; Walley, Nicole M.; Haglund, Michael M.; Radtke, Rodney A.; Skene, J. H. Pate; Sinha, Saurabh R.; Heinzen, Erin L.
Summary: Objective: Hippocampal sclerosis is the most common neuropathologic finding in cases of medically intractable mesial temporal lobe epilepsy. In this study, we analyzed the gene expression profiles of dentate granule cells of patients with mesial temporal lobe epilepsy with and without hippocampal sclerosis to show that next‐generation sequencing methods can produce interpretable genomic data from RNA collected from small homogenous cell populations, and to shed light on the transcriptional changes associated with hippocampal sclerosis. Methods: RNA was extracted, and complementary DNA (cDNA) was prepared and amplified from dentate granule cells that had been harvested by laser capture microdissection from surgically resected hippocampi from patients with mesial temporal lobe epilepsy with and without hippocampal sclerosis. Sequencing libraries were sequenced, and the resulting sequencing reads were aligned to the reference genome. Differential expression analysis was used to ascertain expression differences between patients with and without hippocampal sclerosis. Results: Greater than 90% of the RNA‐Seq reads aligned to the reference. There was high concordance between transcriptional profiles obtained for duplicate samples. Principal component analysis revealed that the presence or absence of hippocampal sclerosis was the main determinant of the variance within the data. Among the genes up‐regulated in the hippocampal sclerosis samples, there was significant enrichment for genes involved in oxidative phosphorylation. Significance: By analyzing the gene expression profiles of dentate granule cells from surgically resected hippocampal specimens from patients with mesial temporal lobe epilepsy with and without hippocampal sclerosis, we have demonstrated the utility of next‐generation sequencing methods for producing biologically relevant results from small populations of homogeneous cells, and have provided insight on the transcriptional changes associated with this pathology.